Penerapan Teknik Self-Control terhadap Kecanduan Game Online pada Mahasiswa - Amanda, Raisa; Solechah, Firda Nikmatus; Jamaluddin, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to know the effectiveness of self-control techniques in decreasing online gaming addiction in a college student. Using the Single Subject Research (SSR) method with an A–B design and a follow-up phase, this study focused on observation of subjects’ gradual changes in behavior through three phases: baseline, intervention, and follow-up. The subjects were selected through purposive sampling techniques based on the criteria of online game addiction according to the theoretical indicators of Chen Chang (2008) as well as Lemmens et al. (2016). The intervention was conducted through self-control techniques for 10 days, accompanied by the use of self-monitoring and behavioral contracts. The study results showed there was a decrease in game playing duration from an average of 3 hours 26 minutes/day in the baseline phase to 1 hour 22 minutes/day in the follow-up phase. Additionally, subjects showed improvements in managing stress more adaptively, a decrease in impulse play, and awareness of the negative impact of addiction. These findings indicate that self-control techniques are effective in modifying online gaming addiction behaviors, as well as supporting the development of preventive strategies against digital addictive behaviors among college students.